Apology unveiled: an exploration of Iban youth’s interactions with elders and peers - Lau, Kimberley Yih Long; Runggol, Christine Jacqueline (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
This study delved into the role of social identity and cultural factors in apologetic communication by examining the apology speech acts employed by Malaysian Iban undergraduates at UiTM Sarawak. Specifically, the research aimed to investigate the influence of social power and cultural factors on the use of Iban apologetic techniques among Malaysian Iban university students in six different apology situations. To gather data, the research utilised Discourse Completion Tasks (DCT), presenting participants with six distinct scenarios that required them to provide an apology in the Iban language. The collected data was then analysed to identify and categorise the apology strategies employed by the participants. By examining the impact of social power and cultural norms on the use of semantic formulas in Iban apologies, this study sheds light on how students’ apologetic strategies are influenced by the social environment and cultural norms. The findings offer valuable insights into intercultural communication within multicultural academic settings. These insights hold significant implications for language teaching and intercultural communication training, emphasising the importance of recognizing and accommodating diverse apology strategies to foster effective communication and mutual understanding among individuals from various social and cultural backgrounds. By shedding light on the sociolinguistic behaviour of Malaysian Iban undergraduates, this study significantly contributes to the field of sociolinguistics and enriches our understanding of cross-cultural communication patterns in apology speech acts. However, it is important to acknowledge certain limitations of this study, including its specific focus on Malaysian Iban undergraduates at UiTM Sarawak, which may limit the generalizability of the findings. Nonetheless, this study provides a foundation for future research in the area of apology speech acts and intercultural communication.